THE EFFECT OF PALM WASTE AND DIFFERENT HARVESTING AGES ON KAILAN PRODUCTION (Brassica oleraceae var. acephala) - Mahmud Chasnawi; Yunida Berliana; Dedi Kurniawan; Erfan Wahyudi (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2022)
The growth and production of kailan is carried out through the use of palm oil waste as a planting medium, the types of waste used are Empty Bunches of Palm Oil (EFB), Dried Decanter Solid (DDS) and Fiber. The purpose of the study was to determine the effect of three types of palm oil waste on the growth and production of kailan, the treatment of differences in harvest age aimed to see the right harvest on kailan plants and then see the interaction of the two treatments in the kailan production phase.This research was conducted in Tunggurono Binjai Timur District, North Sumatra from October 2021 to January 2022. Randomized Group Design (RAK) Factorial with palm waste treatment and harvest age, First factor palm waste M0 = (Top soil), M1 (Top soil + EFB), M2 (Top soil + DDS) and M3 (Top soil + Fiber). The second factor of harvest life is P1 (30 HST), P2 (35 HST) and P3 (40 HST). fresh weight per plant (g), fresh weight per plot (g), root volume (cm3) and dry weight per plant (g). In the Study Randomized Design Group (RAK) Factorial showed that the treatment of palm waste and harvest age had a significant effect on fresh weight per plant, fresh weight per plot, root volume and dry weight per plant. And the interaction of the two had a marked effect on the dry weight per plant, the dry weight per plant was best obtained at the treatment (M2P1) 3.03 g.